2020
DOI: 10.1186/s40168-020-00805-0
|View full text |Cite
|
Sign up to set email alerts
|

Domestication of Oryza species eco-evolutionarily shapes bacterial and fungal communities in rice seed

Abstract: Background: Plant-associated microbiomes, which are shaped by host and environmental factors, support their hosts by providing nutrients and attenuating abiotic and biotic stresses. Although host genetic factors involved in plant growth and immunity are known to shape compositions of microbial communities, the effects of host evolution on microbial communities are not well understood. Results: We show evidence that both host speciation and domestication shape seed bacterial and fungal community structures. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 63 publications
10
101
0
Order By: Relevance
“…Studies on the rhizomicrobiomes of O. sativa and their relative wild accessions O. rufipogon have shown that the domesticated rice is different from wild rice due to its long domestication history and some distinct rhizomicrobial groups of wild rice that were gradually eliminated ( Shenton et al, 2016 ; Tian et al, 2017 ; Chang et al, 2021 ). These observations are in accordance with the hypothesis that the plant host coevolved with their rhizomicrobiomes, and that rhizomicrobial communities are primarily determined by a series of changes due to domestication ( Moran and Sloan, 2015 ; Sasse et al, 2017 ; Kim et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Studies on the rhizomicrobiomes of O. sativa and their relative wild accessions O. rufipogon have shown that the domesticated rice is different from wild rice due to its long domestication history and some distinct rhizomicrobial groups of wild rice that were gradually eliminated ( Shenton et al, 2016 ; Tian et al, 2017 ; Chang et al, 2021 ). These observations are in accordance with the hypothesis that the plant host coevolved with their rhizomicrobiomes, and that rhizomicrobial communities are primarily determined by a series of changes due to domestication ( Moran and Sloan, 2015 ; Sasse et al, 2017 ; Kim et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…All four of the unweighted UniFrac distance matrices of microbial communities were significantly correlated with the genetic distances between the rice genotypes they are associated with (Table S7). This result is consistent with previous studies focusing on wild and modern rice varieties (Shenton et al ., 2016; Kim et al ., 2020), maize and other Poaceae (Bouffaud et al ., 2014) suggesting that the evolutionary history of poaceous crop plants has had an impact on the evolutionary history of their microbial communities.…”
Section: Resultsmentioning
confidence: 99%
“…The microbial community associated with the rice rhizosphere has been the most intensively investigated (Edwards et al ., 2015; Wang et al ., 2016; Edwards et al ., 2018; Moronta‐Barrios et al ., 2018; Ding et al ., 2019). Specifically, several studies have focused on the comparison of the rhizosphere or seed‐associated microbial communities of wild Oryza , rice landraces and modern rice varieties (Shenton et al ., 2016; Shi et al ., 2019; Kim et al ., 2020). For instance, Shenton and colleagues (2016) have shown that the rhizosphere bacterial community of wild Oryza differed substantially from that of cultivated rice in terms of both species richness and composition (Shenton et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial genera such as Curtobacterium, Enterobacter, Methylobacterium, Microbacterium, and Sphingomonas are frequently reported as the core-spermosphere microbiome of rice [68,69]. Kim et al [70] also reported dominance of Pantoea (42.5 %), Methlyobacterium (11.8 %), Curtobacterium (9.3 %), Pseudomonas (8.7 %), andSphingomonas (8.6 %) on rice spermosphere. They also observed that the seed microbiome appeared to be highly stable and protected owing to their natural encapsulation in the seed coat that enables them to be inherited, known as vertical transmission.…”
Section: Discussionmentioning
confidence: 99%